Cardiovascular risk in pediatric type 1 diabetes: sex-specific intima-media thickening verified by automatic contour identification and analyzing systems - Krebs, Andreas; Grulich-Henn, Jürgen (Pediatric diabetes, 2012)
Krebs A, Schmidt-Trucksäss A, Doerfer J, Grulich-Henn J, Holder M, Hecker W, Krebs K, Barth M, Schwab KO. Cardiovascular risk in pediatric type 1 diabetes: sex-specific intima-media thickening verified by automatic contour identification and analyzing systems. Objectives: To improve screening and quantification of subclinical atherosclerosis in children and adolescents with type 1 diabetes (T1D), we investigated the distribution of cardiovascular risk factors (cRFs) and carotid intima-media thickness (cIMT) percentiles with regard to sex-specific differences. Methods: This cross-sectional analysis included clinical parameters, blood lipids, and B-mode ultrasound examination of the bilateral mean cIMT using an automatic contour identification procedure combined with computerized analysis. Results: A total of 270 patients were eligible for evaluation (126 females, mean age 13.7 yr; 144 males, mean age 13.8 yr). In the total group, cIMT was significantly related to sex and diabetes duration but not to age. In males, cIMT was significantly higher than in females and sex-specific cIMT percentiles were calculated. Both pulse pressure and diabetes duration in boys and low-density lipoprotein (LDL)-cholesterol, hemoglobin A1c (HbA1c), and diabetes duration in girls showed a significant association with cIMT. Conclusions: On the basis of sex differences of cRFs and cIMT in pediatric T1D, the assessment of sex-specific IMT percentiles facilitates a differentiated interpretation of subclinical atherosclerosis. The underlying diabetes and additional cRFs seem to be more important determinants of intima-media thickening than age. To improve the comparability of IMT measurements of relevant studies, the international harmonization of IMT measurements should be aimed for.